2022
DOI: 10.1002/adma.202200011
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Solid‐State Ultraviolet B Emitting Carbon Dots via Acetic Acid‐Promoted Fractions of sp3 Bonding Strategy

Abstract: Carbon dots (CDs) have received tremendous attention for their excellent photoluminescence (PL) properties. However, it remains a great challenge to obtain CDs with ultraviolet (UV, 200–400 nm) emission in solid state, which requires strict control of the CDs structure and overcoming the aggregation‐caused quenching (ACQ). Herein, a new sp3 compartmentalization strategy is developed to meet these requirements, by employing acetic acid to promote fractions of sp3 bonding during the synthesis of CDs. It markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…The signal peaks between 6.0 and 9.0 ppm correspond to aromatic protons. 42,[43][44][45][47][48][49] Obviously, with the introduction of N doping, both five-and six-membered ring forms may be present in the CD structure due to the possible structural changes of the CDs caused by N doping. Therefore, compared with the CDs without N doping, the N-doped CDs have significantly more signal peaks between 6.0 and 9.0.…”
Section: Resultsmentioning
confidence: 99%
“…The signal peaks between 6.0 and 9.0 ppm correspond to aromatic protons. 42,[43][44][45][47][48][49] Obviously, with the introduction of N doping, both five-and six-membered ring forms may be present in the CD structure due to the possible structural changes of the CDs caused by N doping. Therefore, compared with the CDs without N doping, the N-doped CDs have significantly more signal peaks between 6.0 and 9.0.…”
Section: Resultsmentioning
confidence: 99%
“…And the picture of ThT‐CDs in EtOH‐H 2 O under 365 nm ultraviolet light showed that the fluorescence intensity began to decrease significantly due to the violent ACQ (aggregation‐caused quenching) effect when f m reached 50 %, which is further demonstrated the existence of aggregated ThT‐CDs (Figure S10) [21] . It can be seen from Figure S11a that with the gradual increase of f m , the fluorescence intensity decreased significantly and appeared red‐shifted, which is due to the ACQ caused by the formation of aggregated ThT‐CDs.…”
Section: Resultsmentioning
confidence: 87%
“…And the picture of ThT-CDs in EtOH-H 2 O under 365 nm ultraviolet light showed that the fluorescence intensity began to decrease significantly due to the violent ACQ (aggregationcaused quenching) effect when f m reached 50 %, which is further demonstrated the existence of aggregated ThT-CDs (Figure S10). [21] It can be seen from Figure S11a that with the gradual increase of f m , the fluorescence intensity decreased significantly and appeared red-shifted, which is due to the ACQ caused by the formation of aggregated ThT-CDs. More specifically, during the process of f m rising from 80 % to 99 % in EtOH-H 2 O containing ThT-CDs, the fluorescence intensity maintained a decreasing and red-shifted trend at the beginning, while reversely increased when it is close to 90 %, and in the remaining 90-99 % of the rising stage, the fluorescence intensity decreased again and blue-shifted (Figure S11b).…”
Section: Resultsmentioning
confidence: 94%
“…Most of the existing first− and second− generation PSs are porphyrins, phthalocyanines, and their derivatives compounds, which are often limited by factors such as poor resistance to photobleaching under light irradiation, heavy metals effect, and low clearance rate from the target tissue [ 8 ]. Carbon dots (CDs) have been presented as a new metal−free carbon nanomaterial due to their abundant surface groups [ 9 , 10 ], superb biocompatibility, good photobleaching resistance, and adjustable optical properties [ 11 ], and many researchers’ works have conducted a series of exploration and attempts at its application in the field of PDT for different types of cancer. Excitingly, it was Ge et al [ 12 ] who discovered for the first time that the synthesized graphene quantum dots (GQDs) have high 1 O 2 yield under light stimulation and are further applied to PDT tumor therapy in living mice.…”
Section: Introductionmentioning
confidence: 99%